Question 25 - Tangents and Normals (using Differentiation) - Chapter 6 Class 12 Application of Derivatives
Last updated at April 16, 2024 by Teachoo
Tangents and Normals (using Differentiation)
Question 2
Question 3 Important
Question 4
Question 5 Important
Question 6
Question 7 Important
Question 8
Question 9 Important
Question 10
Question 11 Important
Question 12
Question 13
Question 14 (i)
Question 14 (ii) Important
Question 14 (iii)
Question 14 (iv) Important
Question 14 (v)
Question 15 Important
Question 16
Question 17
Question 18 Important
Question 19
Question 20
Question 21 Important
Question 22
Question 23 Important
Question 24 Important
Question 25 You are here
Question 26 (MCQ) Important
Question 27 (MCQ)
Tangents and Normals (using Differentiation)
Last updated at April 16, 2024 by Teachoo
Question 25 Find the equation of the tangent to the curve √(3𝑥−2) which is parallel to the line 4x − 2y + 5 = 0 . Let (ℎ , 𝑘) be the point on Curve from tangent to be taken We know that Equation of tangent is 𝑑𝑦/𝑑𝑥 𝑦=√(3𝑥 −2) Differentiating w.r.t.𝑥 𝑑𝑦/𝑑𝑥=(𝑑(3𝑥 −2)^(1/2))/𝑑𝑥 𝑑𝑦/𝑑𝑥=3/(2√(3𝑥 −2)) Slope of tangent at (ℎ , 𝑘) is 〖𝑑𝑦/𝑑𝑥│〗_((ℎ , 𝑘) )=3/(2√(3ℎ − 2)) Given tangent is parallel to the line 4𝑥−2𝑦+5 So , Slope of tangent = Slope of 4𝑥−2𝑥+5 Now, Given line is 4𝑥−2𝑦+5=0 −2𝑦=−4𝑥−5 2𝑦=4𝑥+5 𝑦=(4𝑥 + 5)/2 𝑦=2𝑥+5/2 The above Equation is of the form 𝑦=𝑚𝑥+𝑐 where m is Slope of line ∴ Slope of line is 2 Now, Slope of tangent at (ℎ , 𝑘)= Slope of line 4𝑥−3𝑦+5=0 3/(2√(3ℎ −2))=2 3=2 ×2√(3ℎ −2) 3=4√(3ℎ −2) Squaring Both Sides (3)^2=(4√(3ℎ −2))^2 9=(4)^2 (√(3ℎ −2))^2 9=16(3ℎ −2) 9/16=3ℎ −2 3ℎ −2=9/16 3ℎ=9/16+2 3ℎ=(9 + 32)/16 3ℎ=41/16 ℎ=41/(16 × 3) ℎ=41/48 Now, 𝑦=√(3𝑥 −2) Since Point (ℎ , 𝑘) is on the Curve Point (ℎ , 𝑘) Satisfies the Equation of Curve Putting 𝑥=ℎ , 𝑦=𝑘 𝑘=√(3ℎ −2) Finding k when ℎ=41/48 𝑘=√(3 ×41/48−2) =√(41/16−2)=√((41 −32)/16)=√(9/16)=3/4 Hence the point is (h, k) = (41/48 , 3/4) We know that Equation of line at (𝑥1 , 𝑦1)& having Slope m is 𝑦−𝑦1=𝑚(𝑥−𝑥1) Equation of tangent at (41/48 , 3/4) & having Slope 2 is (𝑦−3/4)=2(𝑥−41/48) (4𝑦 − 3)/4=2((48𝑥 − 41)/48) (4𝑦 − 3)/4=(48𝑥 − 41)/24 24(4𝑦 − 3)/4=48𝑥−41 6(4𝑦−3)=48𝑥−41 24𝑦−18=48𝑥−41 48𝑥−41−24𝑦+18=0 48𝑥−24𝑦−23=0 48𝑥−24𝑦=23 Hence Required Equation of tangent is 𝟒𝟖𝒙−𝟐𝟒𝒚=𝟐𝟑